Effect of New Zealand blueberry consumption on recovery from eccentric exercise-induced muscle damage - McLeay Yanita; Barnes Matthew J; Mundel Toby; Hurst Suzanne M; Hurst Roger D; Stannard Stephen R (Taylor & Francis Group, 2012)
Abstract Background Exercise-induced muscle damage (EIMD) is accompanied by localized oxidative stress / inflammation which, in the short-term at least, is associated with impaired muscular performance. Dietary antioxidants have been shown to reduce excessive oxidative stress; however, their effectiveness in facilitating recovery following EIMD is not clear. Blueberries demonstrate antioxidant and anti-inflammatory properties. In this study we examine the effect of New Zealand blueberries on EIMD after strenuous eccentric exercise. Methods In a randomized cross-over design, 10 females consumed a blueberry smoothie or placebo of a similar antioxidant capacity 5 and 10 hours prior to and then immediately, 12 and 36 hours after EIMD induced by 300 strenuous eccentric contractions of the quadriceps. Absolute peak and average peak torque across the knee, during concentric, isometric, and eccentric actions were measured. Blood biomarkers of oxidative stress, antioxidant capacity, and inflammation were assessed at 12, 36 and 60 hours post exercise. Data were analyzed using a two-way ANOVA. Results A significant (p < 0.001) decrease in isometric, concentric and eccentric torque was observed 12 hours following exercise in both treatment groups. During the 60 hour recovery period, a significant (p = 0.047) interaction effect was seen for peak isometric tension suggesting a faster rate of recovery in the blueberry intervention group. A similar trend was observed for concentric and eccentric strength. An increase in oxidative stress and inflammatory biomarkers was also observed in both treatment groups following EIMD. Although a faster rate of decrease in oxidative stress was observed in the blueberry group, it was not significant (p < 0.05) until 36 hours post-exercise and interestingly coincided with a gradual increase in plasma antioxidant capacity, whereas biomarkers for inflammation were still elevated after 60 hours recovery. Conclusions This study demonstrates that the ingestion of a blueberry smoothie prior to and after EIMD accelerates recovery of muscle peak isometric strength. This effect, although independent of the beverage's inherent antioxidant capacity, appears to involve an up-regulation of adaptive processes, i.e. endogenous antioxidant processes, activated by the combined actions of the eccentric exercise and blueberry consumption. These findings may benefit the sporting community who should consider dietary interventions that specifically target health and performance adaptation.